Study of Latest Trend on Acupuncture for Obesity Treatment - Hea-Sun Chun; Dong-Hwan Kim; Ho-Seub Song (Korean Pharmacopuncture Institute, 2021)
Objectives: The aim of this review was to appraise Korean studies published between 2010 and 2021 which examined the role of acupuncture in the treatment of obesity. Methods : We performed a search of the NDSL, KISS, RISS, OASIS, PubMed, EMBASE electronic databases for relevant animal researches, case reports, and clinical trials, using the following search terms: 'obesity', 'acupuncture', 'electroacupuncture', and 'pharmacopuncture'. We excluded previous reviews and meta-analyses, studies not related to obesity or acupuncture treatment, as well as studies conducted in countries other than Korea. We also excluded studies where relevant information on acupuncture treatment in obesity could not be obtained. Results : Most studies were conducted in animals, followed by case reports and clinical trials. In animal researches and case reports, pharmacopuncture was the most used intervention. In case studies, electroacupuncture, thread-embedding therapy, manual acupuncture, acupotomy, and auricular acupuncture were also used. In animal researches, pharmacopuncture treatment was associated with improvement in obesity indices. In the case of local obesity, specific acupuncture techniques such as thread-embedding therapy and pharmacopuncture were associated with significant improvements in local obesity, even when diet and exercise were not controlled for. Conclusion : Acupuncture treatment showed significant benefit in the treatment of obesity, with a local effect evident for certain approaches, such thread-embedding therapy and acupotomy.